2008
DOI: 10.3390/ijerph2008050021
|View full text |Cite
|
Sign up to set email alerts
|

Sanitary Conditions of Public Swimming Pools in Amman, Jordan

Abstract: Abstract:This study was carried out in the summer of 2005 and investigated all of active public swimming pools (85 out of 93) in Amman, the capital of Jordan. The aim of this study was to find out if these swimming pools are in compliance with Jordanian Standards for Swimming Pools Water (JS 1562(JS /2004. The pools were surveyed against the water microbial quality and other physicochemical parameters indicated in the standards. Two samples from each pool were collected for microbial analysis and pools monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
3
10
1
Order By: Relevance
“…Some pools showed higher indicator bacteria counts before bath suggesting the likely sources of water contamination or poor disinfection process for water supply. Risk of infection caused by pathogenic and non-pathogenic enteric organisms in pools, spas and similar recreational environments have been attributed to the release of materials into water by bathers through human shedding these organisms in faeces, urine, skin, saliva or mucus discharges (APHA, 1998;Castor and Beach, 2004;Rabi et al, 2008). Inadequate residual of a halogen (like chlorine) based disinfectant in these studied pools, increased bathers loads, use of pools by infected persons and low balance in water chemistry, greatly increases the potential for human illnesses (Fleisher et al, 1996;Nnaji et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some pools showed higher indicator bacteria counts before bath suggesting the likely sources of water contamination or poor disinfection process for water supply. Risk of infection caused by pathogenic and non-pathogenic enteric organisms in pools, spas and similar recreational environments have been attributed to the release of materials into water by bathers through human shedding these organisms in faeces, urine, skin, saliva or mucus discharges (APHA, 1998;Castor and Beach, 2004;Rabi et al, 2008). Inadequate residual of a halogen (like chlorine) based disinfectant in these studied pools, increased bathers loads, use of pools by infected persons and low balance in water chemistry, greatly increases the potential for human illnesses (Fleisher et al, 1996;Nnaji et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Jabu et al, (2005) showed that pool water samples were not contaminated with total coliforms because pool water was treated properly. Rabi et al, (2007) reported that 94.7% of swimming pool samples were contaminated with FC. Another study done by Itah and Ekpombok (2004) reported that all of the water samples of the swimming pools were positive for FC.…”
Section: Correlation Between Bacteriological and Physicochemical Paramentioning
confidence: 99%
“…Some studies have been investigated the quality of pool waters during the working days (4,5). Also, some researcher believed the highest number of swimmers during holidays and weekend are young children (16), therefore the water sampling would be better evaluated in these times. In order to monitor the environmental effect of physicochemical and microbial program, we examined the water pool conditions when the pools were disinfected and suitable for swimmers.…”
Section: Discussionmentioning
confidence: 99%